2021
DOI: 10.3389/fmicb.2020.609017
|View full text |Cite|
|
Sign up to set email alerts
|

Considerations for Phage Therapy Against Mycobacterium abscessus

Abstract: There is a global increasing number of Mycobacterium abscessus infections, especially pulmonary infections. Reduced therapeutic options exist against this opportunistic pathogen due to its high intrinsic and acquired levels of antibiotic resistance. Phage therapy is a promising afresh therapy, which uses viruses to lyse bacteria responsible for the infection. Bacteriophages have been recently administered under compassionate use to a 15-year-old patient infected with M. abscessus in combination with antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…In this case, the therapy resulted in decreased size of skin lesions and improvement in lung function, liver function, chest imaging and weight gain. Although this illustrates that phage therapy against NTM infections holds vast potential, there is little understanding of phage-host dynamics in disease environments and a clear lack of pre-clinical studies concerning phage therapy of M. abscessus infections (Senhaji-Kacha et al, 2021). In this context, we studied the GD01mycobacteriophage infection dynamics under various physiological and disease-mimicking conditions using a CF zebrafish model of infection.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the therapy resulted in decreased size of skin lesions and improvement in lung function, liver function, chest imaging and weight gain. Although this illustrates that phage therapy against NTM infections holds vast potential, there is little understanding of phage-host dynamics in disease environments and a clear lack of pre-clinical studies concerning phage therapy of M. abscessus infections (Senhaji-Kacha et al, 2021). In this context, we studied the GD01mycobacteriophage infection dynamics under various physiological and disease-mimicking conditions using a CF zebrafish model of infection.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, the result of a clinical trial on a patient with cystic fibrosis (CF) suffering from a prolonged disseminated infection with M. abscessus , Pseudomonas aeruginosa, EBV viremia (8 years), with a history of two lung transplantations along with administration of various oral/intravenous antibiotics, lumacaftor/ivacaftor, and immunosuppressive drugs (e.g., Clofazimine, bedaquiline, Mycophenolate mofetil, iv rituximab) revealed that the hypodermic administration of mycobacteriophages cocktail containing Muddy (wild type) and engineered BPs33ΔHTH-HRM10 and ZoeJΔ45 every 12 h for seven months (10 9 pfu/dose of each phage) could improve the recovery in this patient [ 16 , 17 , 196 ]. Furthermore, regarding the engineered phages used in the recent study, repressors that induce the lysogenic life cycle in these phages were deleted, and these phages were converted to lytic phages.…”
Section: Mycobacteriophages and Treatment Of Mycobacterial Infectionsmentioning
confidence: 99%
“…Furthermore, regarding the engineered phages used in the recent study, repressors that induce the lysogenic life cycle in these phages were deleted, and these phages were converted to lytic phages. Accordingly, this analysis indicated that the application of mycobacteriophage cocktails could resolve problems caused by phage-resistant M. abscessus strains and temperate phages that were previously integrated into the bacterial genome and contributed to expanding the infection [ 17 ].…”
Section: Mycobacteriophages and Treatment Of Mycobacterial Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteriophage is a potential tool in the treatment of bacterial infection, rapid detection of pathogens, bacterial typing, control of bacterial contamination in food, treatment of environmental pollution, control of pathogen transmission and molecular biology research. [7][8][9][10][11][12][13][14] It has been reported that bacteriophages are used to treat Mycobacterium infections, for example, in 2019, the United States researchers clinically improved one case of cystic fibrosis with disseminated mycobacterial infection by intravenous injection of three mycobacterial bacteriophages. 15 In addition, bacteriophages also have been reported for the treatment of Carbapenem-Resistant Klebsiella pneumoniae, [16][17][18][19] multidrug-resistant Acinetobacter baumannii, 20 pan-drug resistant Pseudomonas aeruginosa et al 21 But we cannot be too blindly optimistic, because we have to face the reality that bacteria are resistant to bacteriophages.…”
Section: Introductionmentioning
confidence: 99%